Emerging technologies in intelligent applications for image and video processing - Santhi, V. 1971-; Acharjya, D. P. 1969-; Ezhilarasan, M. d 1968- e editor (Advances in computational intelligence and robotics (ACIR) book series, 2016)
This book presents the most current research relating to multimedia technologies including video and image restoration and enhancement as well as algorithms used for image and video compression, indexing and retrieval processes, and security concerns